Seed Treatment with Diamide and Neonicotinoid Mixtures for Controlling Fall Armyworm on Corn: Toxicity Evaluation, Effects on Plant Growth and Residuality - Li, Hongbo; Feng, Lei; Fu, Junhong; Zhang, Ying; Huang, Wenyuan; Duan, Tingting; Hu, Yang; Xing, Jichun (Frontiers in Chemistry, 2022)
The diamides, chlorantraniliprole (CHL) and cyantraniliprole (CYA), have been used as seed treatment agents against the fall armyworm (FAW), Spodoptera frugiperda in China. However, large-scale application of these two insecticides is prohibited because of their high cost. The neonicotinoid insecticides, clothianidin (CLO) and thiamethoxam (THI), are cheaper and widely used. In this study, we tested the efficacy of CHL+CLO and CYA+THI as seed treatment agents against FAW larvae both in laboratory and field conditions. Laboratory experiments showed that the two binary mixtures (both 240 g.a.i.100 kg-1 corn seeds) caused FAW mortality exceeded 84.00% at 14 d after seedling emergence (DAE). The mortality of the binary mixtures were similar to either CHL(300 g.a.i.100 kg-1corn seeds) or CYA(144 g a.i.100 kg-1corn seeds), but higher than CLO (120 g.a.i.100 Kg-1corn seeds) or THI (180g a.i.100 kg-1corn seeds). Two independent field experiments showed that both binary mixtures resulted in above 68.00% control efficacy at 14 DAE, suggesting that these insecticidal combinations could effectively control FAW over a relative long period. In addition, both binary mixtures showed no negative effects on the growth and development of corn seedlings. The residues of binary mixtures in corn leave were also lower at 28 DAE as compared to residues in CHL or CYA alone. Most importantly, the costs of CHL+CLO were reduced up to 50% and CYA+THI up to 20% when compared to singly used chemical. Totally, our results indicated that CHL+CLO and CYA+THI had the same control efficacy as CHL or CYA alone, but with much lower cost.